Climate and functional traits jointly mediate tree water‐use strategies. Issue 2 (21st May 2021) - Flo, Victor; Martínez‐Vilalta, Jordi; Mencuccini, Maurizio; Granda, Victor; Anderegg, William R. L.; Poyatos, Rafael
Summary: Tree water use is central to plant function and ecosystem fluxes. However, it is still unknown how organ‐level water‐relations traits are coordinated to determine whole‐tree water‐use strategies in response to drought, and whether this coordination depends on climate. Here we used a global sap flow database (SAPFLUXNET) to study the response of water use, in terms of whole‐tree canopy conductance ( G ), to vapour pressure deficit (VPD) and to soil water content (SWC) for 142 tree species. We investigated the individual and coordinated effect of six water‐relations traits (vulnerability to embolism, Huber value, hydraulic conductivity, turgor‐loss point, rooting depth and leaf size) on water‐use parameters, also accounting for the effect of tree height and climate (mean annual precipitation, MAP). Reference G and its sensitivity to VPD were tightly coordinated with water‐relations traits rather than with MAP. Species with efficient xylem transport had higher canopy conductance but also higher sensitivity to VPD. Moreover, we found that angiosperms had higher reference G and higher sensitivity to VPD than did gymnosperms. Our results highlight the need to consider trait integration and reveal the complications and challenges of defining a single, whole‐plant resource use spectrum ranging from 'acquisitive' to 'conservative'.